Description of Socialization Ability in Isolation Patients - Pragholapati, Andria; Muliani, Rizki; Wiratama, Naricho Yudha (JOSING: Journal of Nursing and Health, 2022)
This study aims to describe the socialization ability of social isolation patients at the Mental Hospital of West Java Province. The research method used is quantitative with a cross-sectional design. The study results based on the Shapiro-Wilk test between socialization skills obtained a p-value of 0.709 which means it is more significant than 0.05, so it can open up opportunities for socialization to isolated patients in West Java. The Provincial Mental Hospital is good. In conclusion, the respondents in this study in terms of affective aspects cognitive aspects can be categorized as good. Keywords: Mental Disorders, Psychiatric Hospital, Socialization Capability, Social Isolation